Synthesis of new water soluble silicon phthalocyanine substituted by linker sulfur atom and photophysicochemical studies for photodynamic therapy - Atmaca, Goknur Yasa; Erdogmus, Ali (WORLD SCIENTIFIC PUBL CO PTE LTD, 2019)
In this work, 5-(trifluoromethyl)-2-thiopyridine substituted SiPc (1) and its quaternized derivative (2) were synthesized, and the effect of the linker sulfur atom on silicon phthalocyanines has been investigated for the first time in the literature. Both of the complexes have been characterized by standard spectroscopy methods. The complexes have good solubility in organic solvents and showed monomeric tendencies in all studied solvents. Only complex 2 had some aggregation in water because of solvent effects, as expected. In order to determine the therapeutic effect for cancer treatment, photophysicochemical properties were investigated in DMSO, DMF, toluene and water (for complex 2). The synthesized complexes were found to have about 3.5 times higher singlet oxygen quantum yields than the yields of unsubstituted SiPcCl2 (Phi(Delta) = 0.15 (in DMSO), 0.12 (in DMF), 0.10 (in toluene)) because of the effects of bulky axial groups.
Keywords: silicon phthalocyanine; singlet oxygen quantum yield; photodynamic therapy; METAL-FREE; METALLOPHTHALOCYANINES; Chemistry